2013
DOI: 10.1007/8904_2013_227
|View full text |Cite
|
Sign up to set email alerts
|

A Clinically Severe Variant of β-Mannosidosis, Presenting with Neonatal Onset Epilepsy with Subsequent Evolution of Hydrocephalus

Abstract: b-Mannosidosis results from a functional deficiency of the lysosomal enzyme, b-mannosidase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Furthermore, two sequence variants found in ruminants are suggested to abolish the β-mannosidase enzyme activity, resulting in the severe neurodegenerative phenotype (Leipprandt et al 1996, 1999). Comparing patients reported in the literature, no clear genotype–phenotype correlation could be shown in humans (Bedilu et al 2002; Broomfield et al 2013), and variability is suggested to be due to the involvement of other genetic and environmental factors (Gort et al 2006; Riise Stensland et al 2008; Lovell et al 2014). However, comparative structural bioinformatics analyses of inherited mutations reported in MANBA until 2011 indicated the existence of genotype–phenotype correlation in β-mannosidosis (Huynh et al 2011).…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…Furthermore, two sequence variants found in ruminants are suggested to abolish the β-mannosidase enzyme activity, resulting in the severe neurodegenerative phenotype (Leipprandt et al 1996, 1999). Comparing patients reported in the literature, no clear genotype–phenotype correlation could be shown in humans (Bedilu et al 2002; Broomfield et al 2013), and variability is suggested to be due to the involvement of other genetic and environmental factors (Gort et al 2006; Riise Stensland et al 2008; Lovell et al 2014). However, comparative structural bioinformatics analyses of inherited mutations reported in MANBA until 2011 indicated the existence of genotype–phenotype correlation in β-mannosidosis (Huynh et al 2011).…”
Section: Discussionmentioning
confidence: 79%
“…So far, to our knowledge, only 22 cases of β-mannosidosis in 18 families from a range of ethnic backgrounds have been reported since the disease was first described in 1986 (Cooper et al 1986; Wenger et al 1986). The disease has a highly variable clinical presentation (Bedilu et al 2002; Riise Stensland et al 2008) including intellectual disability/developmental delay, behavioral disturbance, recurrent infections, hearing loss, and severe neurological phenotypes such as epileptic encephalopathy, hydrocephalus, and spinocerebellar ataxia (Sedel et al 2006; Labauge et al 2009; Broomfield et al 2013). Dysmorphic traits have been reported (Poenaru et al 1992; Labauge et al 2009).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The encoded protein localizes to the lysosome where it is the final exoglycosidase in the pathway for N-linked glycoprotein oligosaccharide catabolism. Mutations in this gene cause beta-mannosidosis, including severe forms with neonatal onset epilepsy [ 171 ]. RSC1A1 gene product regulates the neuronal expression of the Na + -D-glucose cotransporter SGLT1, which is increased in the hippocampus during epileptic seizures [ 172 ].…”
Section: Resultsmentioning
confidence: 99%